2020
DOI: 10.1038/s41598-020-62888-x
|View full text |Cite
|
Sign up to set email alerts
|

Shut down of the South American summer monsoon during the penultimate glacial

Abstract: We analysed changes in mean annual air temperature (MAAt), vegetation and biomass burning on a long and continuous lake-peat sediment record from the colônia basin, southeastern Brazil, examining the responses of a wet tropical rainforest over the last 180 ka. Stronger southern atmospheric circulation up to the latitude of colônia was found for the penultimate glacial with lower temperatures than during the last glacial, while strengthening of the South American summer monsoon (SASM) circulation started during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 81 publications
2
31
0
1
Order By: Relevance
“…The collaborative nature of the AF BIOTA project enabled several high impact publications. Among other journals, our findings have been published in Scientific Reports (Azevedo et al 2019, De-Silva et al 2017, Pinaya et al 2019, Rodríguez-Zorro et al 2020, Utida et al 2019, Nature Communications (Deininger et al 2020, Science Advances (Rozendaal et al 2019, Thom et al 2020, Nature Ecology and Evolution (Poorter et al, 2019), Proceedings of the National Academy of Science of the United States of America (Cheng et al 2020, Prates et al 2016b, Stríkis et al 2018, Proceedings of the Royal Society of London (Carnaval et al 2014), and Evolution (Amaral et al 2021.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The collaborative nature of the AF BIOTA project enabled several high impact publications. Among other journals, our findings have been published in Scientific Reports (Azevedo et al 2019, De-Silva et al 2017, Pinaya et al 2019, Rodríguez-Zorro et al 2020, Utida et al 2019, Nature Communications (Deininger et al 2020, Science Advances (Rozendaal et al 2019, Thom et al 2020, Nature Ecology and Evolution (Poorter et al, 2019), Proceedings of the National Academy of Science of the United States of America (Cheng et al 2020, Prates et al 2016b, Stríkis et al 2018, Proceedings of the Royal Society of London (Carnaval et al 2014), and Evolution (Amaral et al 2021.…”
mentioning
confidence: 65%
“…Led by collaborator Ledru, the chronostratigraphic analysis of the core revealed that it spans the last 1.5 million years and that the Colônia basin formed between 11.2-5.3 million years ago (Simon et al 2020). Data from the top portion of the core (180,000 years ago [180 ka] until the present) indicated that: 1) a cool mixed evergreen forest was present in the region between 180 and 45 ka, being replaced by rainforest, 2) the temperature around 57-29 ka (penultimate glacial period) was cooler than during the Last Glacial Maximum (23-29 ka), and 3) wet summer season became longer from 95 ka until the present (Rodríguez-Zorro et al 2020). These results show that tropical forest dynamics display different patterns than mid-latitude areas during the last 180 ka, and demonstrate the importance of paleoecological data to help draw a more detailed scenario of the AF vegetation dynamics through time.…”
Section: Academicmentioning
confidence: 99%
“…• steady-state infiltration and constant carbon input. Although relatively small cyclical variations of climate in Brazil over the last few 100, 1,000 years (Cruz et al, 2005;Rodríguez-Zorro et al, 2020) were encountered, the uncertainty of our estimates remains very high; • the plagioclase rate dissolution is pH-independent. Some studies point to the significant dependence on pH values (Gudbrandsson et al, 2014); • the geometry of the model domain is very simple, although it captures the concentration patterns observed in NE part of the aquifer; • only Ca-Na plagioclase is reacting with DIC, whereas in reality there is a competition among the mineral assemblage for a reactant (Oelkers et al, 2018) leading to geochemical heterogeneity and uneven evolution of porous media (Seigneur et al, 2019).…”
Section: Limitations and Additional Considerationsmentioning
confidence: 79%
“…This extrapolation is necessary because we have data for almost all proxies in this secction, so it seems recommendable to indicate the expected ages for the observed changes. We emphasize that this strategy is widely used in Quaternary studies (De Oliveira et al, 2019;Rodríguez-Zorro et al, 2020).…”
Section: Proxies: Meaning and Interpretationmentioning
confidence: 99%